2023
DOI: 10.1177/10732748231185047
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Quality of Life is a Strong and Independent Prognostic Factor for Overall Survival in Metastatic Colorectal Cancer

Abstract: Background Previous studies have established that higher baseline quality of life (QOL) scores are associated with improved survival in patients with metastatic colorectal cancer (mCRC). We examined the relationship between overall survival (OS) and baseline QOL. Patients and Methods A total of 1 247 patients with mCRC participating in N9741 (comparing bolus 5-FU/LV, irinotecan [IFL] vs infusional 5-FU/leucovorin [LV]/oxaliplatin [FOLFOX] vs. irinotecan/oxaliplatin [IROX]) provided data at baseline on overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…There are no randomized controlled trials of reduced-intensity chemotherapy in patients aged ≥80 years with lymphoma. Appropriate reduced-intensity chemotherapies have not been established, and only two phase II trials for DLBCL have been reported [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no randomized controlled trials of reduced-intensity chemotherapy in patients aged ≥80 years with lymphoma. Appropriate reduced-intensity chemotherapies have not been established, and only two phase II trials for DLBCL have been reported [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%